Laced steel–concrete composite sandwich system in flexure: Experiments, analysis and design. (February 2021) - Verma, Mohit; Anandavalli, N; Prakash, Amar; Rajasankar, J
Steel–concrete sandwich composite system consists of steel skin and concrete core. The aim of this paper is to present methods for analysis and preliminary design of a recently developed new class of sandwich composite system laced steel–concrete composite for flexural loads. In laced steel–concrete composite system, continuous lacings are used in place of discrete shear connectors which are generally welded to the skin of the composite. Specimen laced steel–concrete composite systems were subjected to laboratory-controlled experimental investigations. Subsequently, three analytical methods are formulated for evaluating the moment–curvature relation of laced steel–concrete composite system. All the methods exploit the prismatic nature of the laced steel–concrete composite system to derive the moment–curvature relation and employ virtual work principle to evaluate the deflection of the laced steel–concrete composite system. In the first method, the stress–strain relationship of the steel and concrete in tension and compression is utilized to analyse the cross-section of laced steel–concrete composite system. In the second method, fibre-based analysis is used to obtain the response of laced steel–concrete composite system. The third method is based on equivalent transformed section in which the tensile stress–strain behaviour of concrete is represented by an equivalent area under tension. The methods are validated by comparing the predicted values with those of the two- and multi-point loading experiments carried out on laced steel–concrete composite beam and one-way laced steel–concrete composite slab, respectively. All the three methods are found to satisfactorily predict the response of laced steel–concrete composite system. A limited parametric study is carried out by using these analytical methods to identify the role played by the lip and web of the cover plates, tensile strength of concrete and confinement of concrete on the structural response of the laced steel–concrete composite system. In the end, guidelines and charts which can be used for preliminary design of laced steel–concrete composite system for flexure loads are presented.